Private Net Benefits from Afforesting Marginal Cropland and Shrubland with Cork Oaks in Spain - Ovando, Paola; Campos, Pablo; Oviedo, José L.; Montero, Gregorio (Forest Science, 2010)
We estimate the private net benefits from afforesting marginal shrubland and cropland with cork oaks at two Spanish cork oak sites, Aljibe and Gavarres, in different time horizon frames. The analysis integrates market and nonmarket (landowner amenity) private capital incomes, including government afforestation grants. We apply cost-benefit analysis techniques for estimating the investment present value in the periods analyzed, taking residual values of cork oak woodland into account. The results show that the profitability rate of cork oak afforestation strongly depends on government subsidies. The value of private amenities, at least in Aljibe, seems to be positively affected by the forest area's share of the total estate surface. Thus, an increase in the afforested area would enhance the private amenity annual income with respect to maintaining the original property land's treeless uses. A higher level of private amenities attached to the forest area may imply a reduction in government grants for encouraging cork oak afforestation.
Keywords: cost-benefit analysis; government grants; market incomes; private amenity

Accounting for single and aggregated forest incomes: Application to public cork oak forests in Jerez (Spain) and Iteimia (Tunisia) (Ecological Economics, 2008)
This study presents an applied improvement in the agroforestry accounting system (AAS) approach to two public cork oak forests in the Mediterranean region: Jerez (Spain) and Iteimia (Tunisia). Both forests have similar environments but differ in land property rights, labour markets and countries (developed and developing economy, respectively). The income analysis considers the differences between forest ownership, and household and landowner economic rationalities. In the case of Jerez, the public landowner has a right to exclude others from using the forest resources; community employment and natural resource conservation criteria determine Jerez's management. In the Iteimia case, the public landowner has regulated free-use rights for livestock grazing, firewood and crops so that local households can meet their needs and improve their income. Households operate by maximizing their income from the full employment of their own family workforce. The results show that Jerez's management generates negative commercial capital income for the public landowner, despite receiving significant public subsidies, while it maintains high internal forestry investment that generates additional local employment. Conversely, Iteimia produces positive commercial capital income for the public landowner and high household self-employed labour income per hectare.

Does private income support sustainable agroforestry in Spanish dehesa? - Campos, Pablo; Ovando, Paola; Montero, Gregorio (Land Use Policy, 2008)
Oak woodland dehesa suffers from the aging of trees without a natural regeneration of young oaks coming in to replace them. Recent European Union (EU) policy reforms for rural development focus on supporting multifunctional agriculture that complies with the EU’s environmental goals, such as mitigating biodiversity losses and climate change. Such reforms could result in government support for natural woodland regeneration practices in European agroforestry systems, which are recognized for providing valuable environmental services. Managing dehesa cork oak and holm oak woodlands to stimulate the growth of new oaks could be an efficient option for maintaining, and even increasing, the dehesa’s current carbon stock and biodiversity. Here we develop and apply a new agroforestry accounting system based on the concept of Hicksian income to a dehesa in the Monfragu¨ e area of western Spain, using primary microeconomic data from a large case study. Private total income and profitability rates are measured for individual goods and services, and for the entire dehesa in a steady state. Our application extends the EU system of accounts for agriculture and forestry by including private amenity consumption by landowners and the gain or loss in human-made and natural capital. We compare an actual typical unsustainable woodland management scenario with an ideal sustainable management scenario in which there is a continuous regeneration and recruitment of holm and cork oaks as predicted by silvicultural models. The results show that, given current land use policy incentives, allowing a slow depletion of oak trees is more profitable for a dehesa private landowner than maintaining the dehesa’s trees. As a result many dehesa environmental services are gradually lost. This market failure requires new land use policies that induce private land owners to invest in the renewal of aging oak woodlands. To evaluate the impacts of this new policy, we show how private landowner income is affected when changes are made to achieve sustainable management of dehesa oaks. More research is needed in order to understand how the dehesa’s landowner market income and private amenities trade-off can affect the owner’s land use preferences and decisions.
Keywords: Amenities; environmental services; Monte; Oak silviculture; Rural development policy; Total income

Does private income support sustainable agroforestry in Spanish dehesa? (Land Use Policy, 2008)
Oak woodland dehesa suffers from the aging of trees without a natural regeneration of young oaks coming in to replace them. Recent European Union (EU) policy reforms for rural development focus on supporting multifunctional agriculture that complies with the EU’s environmental goals, such as mitigating biodiversity losses and climate change. Such reforms could result in government support for natural woodland regeneration practices in European agroforestry systems, which are recognized for providing valuable environmental services. Managing dehesa cork oak and holm oak woodlands to stimulate the growth of new oaks could be an efficient option for maintaining, and even increasing, the dehesa’s current carbon stock and biodiversity. Here we develop and apply a new agroforestry accounting system based on the concept of Hicksian income to a dehesa in the Monfragu¨ e area of western Spain, using primary microeconomic data from a large case study. Private total income and profitability rates are measured for individual goods and services, and for the entire dehesa in a steady state. Our application extends the EU system of accounts for agriculture and forestry by including private amenity consumption by landowners and the gain or loss in human-made and natural capital. We compare an actual typical unsustainable woodland management scenario with an ideal sustainable management scenario in which there is a continuous regeneration and recruitment of holm and cork oaks as predicted by silvicultural models. The results show that, given current land use policy incentives, allowing a slow depletion of oak trees is more profitable for a dehesa private landowner than maintaining the dehesa’s trees. As a result many dehesa environmental services are gradually lost. This market failure requires new land use policies that induce private land owners to invest in the renewal of aging oak woodlands. To evaluate the impacts of this new policy, we show how private landowner income is affected when changes are made to achieve sustainable management of dehesa oaks. More research is needed in order to understand how the dehesa’s landowner market income and private amenities trade-off can affect the owner’s land use preferences and decisions.

Forestaciones con encina y alcornoque en el área de la dehesa en el marco del (Revista Española de estudios agrosociales y pesqueros, 2007)
La Unión Europea adopta en el año 1992 una serie de medidas de acompañamiento a la reforma de la política agraria común. La política de abandono de tierras agrícolas dedicadas a cultivos excedentarios fue incentivada mediante ayudas a su forestación, reguladas por el Reglamento 2080/1992. Esta intervención pública ha tenido en el área de la dehesa española una influencia favorable a la expansión de sus dos especies forestales más emblemáticas: la encina (Quercus ilex) y el alcornoque (Quercus suber ). La superficie forestada con encina y alcornoque entre 1993 y 2000 supera las 281.000 hectáreas en las comunidades autónomas de Andalucía, Castilla-La Mancha, Castilla y León, Extremadura y Madrid, que concentran alrededor del 95 por ciento de la superficie forestada con ambas especies en España. Este estudio tiene como objetivo ofrecer un análisis descriptivo de los efectos de las forestaciones con encina y alcornoque en los cambios de usos del suelo, así como la influencia que ha tenido la distribución del gasto público en las Comunidades Autónomas del área de la dehesa, en aplicación del Reglamento (CE) 2080/1992.

Forestaciones con encina y alcornoque en el área de la dehesa en el marco del - Ovando, Paola; Campos, Pablo; Montero, Gregorio (Revista Española de estudios agrosociales y pesqueros, 2007)
La Unión Europea adopta en el año 1992 una serie de medidas de acompañamiento a la reforma de la política agraria común. La política de abandono de tierras agrícolas dedicadas a cultivos excedentarios fue incentivada mediante ayudas a su forestación, reguladas por el Reglamento 2080/1992. Esta intervención pública ha tenido en el área de la dehesa española una influencia favorable a la expansión de sus dos especies forestales más emblemáticas: la encina (Quercus ilex) y el alcornoque (Quercus suber ). La superficie forestada con encina y alcornoque entre 1993 y 2000 supera las 281.000 hectáreas en las comunidades autónomas de Andalucía, Castilla-La Mancha, Castilla y León, Extremadura y Madrid, que concentran alrededor del 95 por ciento de la superficie forestada con ambas especies en España. Este estudio tiene como objetivo ofrecer un análisis descriptivo de los efectos de las forestaciones con encina y alcornoque en los cambios de usos del suelo, así como la influencia que ha tenido la distribución del gasto público en las Comunidades Autónomas del área de la dehesa, en aplicación del Reglamento (CE) 2080/1992.
Keywords: alcornoque (PG); cambio de uso; Dehesa; encina; forestación de tierras agrarias